2015
DOI: 10.1002/elan.201500357
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy for Determination of Paracetamol in the Presence of Morphine Using a Carbon Paste Electrode Modified with CdO Nanoparticles and Ionic Liquids

Abstract: A voltammetric sensor for determination of paracetamol in the presence of morphine is described for the first time. The synthesized CdO nanoparticles were characterized with different methods such as scanning electron microscopy (SEM) and X‐ray diffraction (XRD). The paracetamol and morphine peaks are separated ca. 0.37 and 0.65 V, respectively; hence paracetamol can be analysed in the presence of morphine and more than 21 times of the current excess of paracetamol. The detection limits for paracetamol and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…According to previously published papers and the structure of acetaminophen and domperidone , we found that the electro‐oxidation behavior of these drugs is relative to the pH of the solution; this factor is optimized in the first step. The cyclic voltammograms of 5 μM acetaminophen (Figure a 1 ) and 10 μM domperidone (Figure b 1 ) were recorded at a different pH on the surface of the GCE/AgNPs‐PHEMA‐CMK‐1.…”
Section: Resultsmentioning
confidence: 98%
“…According to previously published papers and the structure of acetaminophen and domperidone , we found that the electro‐oxidation behavior of these drugs is relative to the pH of the solution; this factor is optimized in the first step. The cyclic voltammograms of 5 μM acetaminophen (Figure a 1 ) and 10 μM domperidone (Figure b 1 ) were recorded at a different pH on the surface of the GCE/AgNPs‐PHEMA‐CMK‐1.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the linear regression equation for the square root of scan rate vs peak current (shown in inset) was demonstrated with the high correlation coefficient of 0.9964. To analyse the rate determining process, the slope of the tafel plot for scan rate of 20 mV s −1 was calculated of about 8.6131 V −1 decade is equal to n(1−α)F/2.3RT . Accordingly, the charge transfer coefficient value was calculated as α=0.49 from Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of ionic liquids have been exploited in various applications ranging from energy storage and conversion to metal deposition, and they have been used in chemistry, biochemistry and even biomechanics. Recently, Ionics liquid have been attracted tremendous attention in electrochemistry due to their catalytic activity, good electrical conductivity, high sensitivity and their broad electrochemical window . They have recently been used as a new type of modifier for the fabrication of carbon‐based electrodes (CPEs) .…”
Section: Introductionmentioning
confidence: 99%